2009
DOI: 10.1073/pnas.0911606106
|View full text |Cite
|
Sign up to set email alerts
|

Transition state analogues in structures of ricin and saporin ribosome-inactivating proteins

Abstract: Ricin A-chain (RTA) and saporin-L1 (SAP) catalyze adenosine depurination of 28S rRNA to inhibit protein synthesis and cause cell death. We present the crystal structures of RTA and SAP in complex with transition state analogue inhibitors. These tight-binding inhibitors mimic the sarcin-ricin recognition loop of 28S rRNA and the dissociative ribocation transition state established for RTA catalysis. RTA and SAP share unique purine-binding geometry with quadruple -stacking interactions between adjacent adenine a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
77
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(85 citation statements)
references
References 44 publications
(69 reference statements)
8
77
0
Order By: Relevance
“…5). Previous studies have identified that Glu-177 is critical for the depurination activity of ricin (5,6,9,12). Taken together, these data suggested that the ␣-helix may modulate the enzymatic activity of ricin by controlling the side chain orientation of Glu-177.…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…5). Previous studies have identified that Glu-177 is critical for the depurination activity of ricin (5,6,9,12). Taken together, these data suggested that the ␣-helix may modulate the enzymatic activity of ricin by controlling the side chain orientation of Glu-177.…”
Section: Discussionsupporting
confidence: 60%
“…Recently, the transition state analogues in structures of ricin and saporin ribosome-inactivating proteins were studied. The data confirmed that the invariant residues of RIPs in the catalytic active site of ricin were essential for the efficient catalysis by RTA (9). Although the biochemical properties of RIPs have been extensively studied, the enzymatic mechanism of RIPs is still elusive.…”
supporting
confidence: 67%
See 1 more Smart Citation
“…The epitope mainly con-tains the residues Asp 96 -Thr 116 , which forms the substrate binding pocket together with the residues Gly 120 -Asn 136 and residues Asp 201 -Ser 221 (7). To investigate whether 6C2 binding to RTA will change its structure near the enzyme activity center and eliminate the rRNA depurination activity of RTA, we compared the apo-form RTA (PDB code 2AAI) with the RTA in complex with 6C2 and a substrate analog (PDB codes 4KUC and 3HIO).…”
Section: Resultsmentioning
confidence: 99%
“…Recently, the structure of ricin was solved with transition state analogues bound, confirming that these invariant residues of the RIPs in the catalytic active site of ricin were essential for efficient catalysis by RTA (7). Although the biochemical properties of RIPs have been extensively studied, the enzymatic mechanism of RIPs remains elusive.…”
mentioning
confidence: 99%